Nurse training in self-management of patients with cardiovascular diseases: a multicentre observational study - La Sala, Rachele; Dicembrino, Rita Bruna; Dall’Argine, Simona; Baiguera, Monica; Gazzotti, Lorena; Gubin, Elena; Rondini, Alessia; Mamei, Ilaria (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: The therapeutic education and self-management carried out by nurses, are winning elements in cardiovascular secondary prevention, but because they are complex matters, they require special training by the professionals. The target of the study has been to assess the effects in clinical practice of a training program for nurses in the management of patients with cardiovascular diseases, leaning towards a self-oriented patient management and therapeutic patient education. Method: The research utilized a quali-quantitative study to compare the responses of 53 trained nurses (experimental group) and 101 untrained nurses (control group). The instrument used was a self-report structured in two sections: the first, a qualitative kind, was used to investigate the portrayal of nurses regarding self-management; the second, a quantitative kind, included a Likert scale based on 5 points (1=never, 5=always) that investigated the professional nurse’s action in its bio-psycho-socio-relational and clinical activities (La Sala, 2012). Results: The trained nurses’ approach is more oriented towards the psycho-socio-relational dimension, compared to the untrained nurses. A difference also emerged regarding activities of a bio clinical nature, which are performed much more by untrained nurses compared to trained professionals. Conclusions: The health education and self-management skills were used by trained nurses during their care of patients with cardiovascular diseases, stressing the importance for professional nurses to develop an integrated competence, using narrative talks as the main tool in a patient-centred approach.